Flexible Screen-Printed Electrode for Cortisol Detection Based on Sulfur-Doped Graphene/Gold Nanoparticles Conductive Ink - Umuksuz, Hazal; Uruc, Selen; Dokur, Ebrar; Gorduk, Ozge; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2025)
Cortisol (COR), a glucocorticoid hormone synthesized by the adrenal gland and commonly referred to as the stress hormone, plays a crucial role in the regulation of numerous physiological processes in humans. For this reason, the ability to quantify COR rapidly and accurately is of significant importance. In this study, a paper-based flexible electrochemical sensor was developed for the determination of COR utilizing a conductive ink. Sulfur-doped graphene (S-G), synthesized using Yucel's method, and gold nanoparticles (AuNPs) were used as conductive materials, and conductive inks with this composition were developed. The conductive ink was integrated onto paper substrates via screen printing to form flexible electrodes. The optimum conditions for sensor fabrication were identified, and electrochemical, chemical, and morphological characterizations were conducted. The sensor exhibited a detection limit of 15.39 ng mL-1, and its economical and user-friendly design renders it an advantageous option for practical applications. The results obtained from the analytical studies indicated that the sensor demonstrated stability and reproducibility for COR measurement. In conclusion, the proposed flexible sensor can be regarded as a model for future flexible and wearable studies. S-G and AuNPs based conductive ink was developed for direct COR determination.Optimizations were implemented in the S-G/AuNPs ink.The characterization studies of flexible S-G/AuNPs/SPE were carried out.To examine the applicability of SPE in real samples, artificial sweat was studied.
Keywords: cortisol; non-enzymatic; flexible sensor; conductive ink; screen printed electrode; ELECTROCHEMICAL DETERMINATION; SENSORS; SALIVA; Materials Science; Physics